Strategi Pembelajaran Hybrid (Luring-Daring) Mata Pelajaran Agama Hindu di SMA Dwijendra Denpasar Pada Era Pasca-Pandemi - Negara, Gede Agus Jaya (Jayapangus Press, 2025)
The COVID-19 pandemic has accelerated the transformation of global education, including Hindu religious instruction, which emphasizes spiritual values and traditional practices. This shift demands adaptive learning strategies that preserve the essence of religious teachings while remaining responsive to technological advancements. This study aims to analyze the hybrid learning strategy (offline-online) implemented in Hindu religious education at SMA Dwijendra Denpasar, assess its challenges and opportunities, and evaluate the effectiveness of the applied model. A qualitative approach with a case study design was employed, using data collected through in-depth interviews, participatory observation, and document analysis. The findings reveal that the developed model successfully integrates cognitive, affective, and spiritual dimensions through interactive approaches such as virtual pilgrimages, gamification, and digital journaling. In addition to increasing students’ motivation and participation, this strategy redefines the teacher’s role into that of a spiritually grounded facilitator utilizing technology. Nevertheless, several challenges persist, including digital access inequality, limitations in translating sacred experiences into digital formats, and the complexity of managing multimodal instruction. Even so, innovations such as the Virtual Pura and digital peer mentoring systems have helped overcome some of these barriers. The study concludes that a value-based and contextually grounded hybrid learning strategy can foster authentic, adaptive, and transformative religious learning experiences in the post-pandemic era.